Valorisation d’une argile provenant du gisement de M’Zila (Mostaganem) dans le domaine de la dépollution des effluents de l'industrie textile - CHABANE, HADJER (My University, 2016)
The used natural clay, which comes from M'Zila deposit Mostaganem, was purified by sedimentation. The lower fraction was 2 μm is sodium-exchanged, and then washed several times until chloride ions disappeared. The different physical and chemical analyzes showed that the clay phase is illitesmectite is dominant smectite interlayer containing kaolinite and its cation exchange capacity is about 70 meq / 100g. The study of the removal of a synthesis of dye: Rhodamine B by sorption on the purified clay suggests that the tested clay could constitute interesting supports for the trapping of Rhodamine B. Solutions containing from 0.05 to 0.3 mmole/l of Rhodamine B were successfully treated. The adsorption capacity of the clay is close to 60 meq/100 g.
Keywords: Deposit of clay; Rhodamine B; sorption; water treatment; Argile de gisement; Rhodamine B; sorption; traitement des eaux; معدن; الطين منجمي; ملون رودامين; امتصاص; معالجة المياه